Activated protein C resistance in patients with central retinal vein occlusion - Larsson, J (1997)
AIM/BACKGROUND—A new defect in the anticoagulant system has recently been discovered—activated protein C resistance. The frequency of this disorder has been shown to be increased in young patients (<50 years of age) with central retinal vein occlusion. This study was carried out to determine if there was any overrepresentation of activated protein C resistance in patients >50 years of age with central retinal vein occlusion. METHODS—Blood samples were obtained from 83 patients >50 years of age and with a history of central retinal vein occlusion. The blood samples were analysed for activated protein C resistance with standard clinical laboratory methods. RESULTS—In this material 11% of the patients were resistant to activated protein C. The normal incidence of activated protein C resistance in the same geographical area is 10-11%. CONCLUSION—Activated protein C resistance does not seem to be a cause of central retinal vein occlusion in people older than 50( )years.